Plastome-wide comparison reveals new SNV resources for the authentication of Dendrobium huoshanense and its corresponding medicinal slice (Huoshan Fengdou) - Zhitao Niu; Jiajia Pan; Qingyun Xue; Shuying Zhu; Wei Liu; Xiaoyu Ding (Elsevier, 2018)
Dendrobium species and their corresponding medicinal slices have been extensively used as traditional Chinese medicine (TCM) in many Asian countries. However, it is extremely difficult to identify Dendrobium species based on their morphological and chemical features. In this study, the plastomes of D. huoshanense were used as a model system to investigate the hypothesis that plastomic mutational hotspot regions could provide a useful single nucleotide variants (SNVs) resource for authentication studies. We surveyed the plastomes of 17 Dendrobium species, including the newly sequenced plastome of D. huoshanense. A total of 19 SNVs that could be used for the authentication of D. huoshanense were detected. On the basis of this comprehensive comparison, we identified the four most informative hotspot regions in the Dendrobium plastome that encompass ccsA to ndhF, matK to 3'trnG, rpoB to psbD, and trnT to rbcL. Furthermore, to established a simple and accurate method for the authentication of D. huoshanense and its medicinal slices, a total of 127 samples from 20 Dendrobium species including their corresponding medicinal slices (Fengdous) were used in this study. Our results suggest that D. huoshanense and its medicinal slices can be rapidly and unequivocally identified using this method that combines real-time PCR with the amplification refractory mutation system (ARMS). KEY WORDS: Dendrobium huoshanense, Plastome, Slices, Single nucleotide variants, RT-ARMS, Authentication